Comparison of and as Reporter Genes for Noninvasive Imaging of Bone Mesenchymal Stem Cells Transplanted into Infarcted Rat Myocardium - Shuo Hu; Wei Cao; Xiaoli Lan; Yong He; Juntao Lang; Congjiao Li; Jia Hu; Rei An; Zairong Gao; Yongxue Zhang (Molecular Imaging)
The purpose of this study was to investigate and compare the feasibility of rat sodium iodide symporter ( rNIS ) and human sodium iodide symporter ( hNIS ) as reporter genes for noninvasive monitoring of rat bone marrow mesenchymal stem cells (rBMSCs) transplanted into infarcted rat myocardium. rBMSCs were isolated from rat bone marrow. Adenovirus (Ad) was reconstructed to contain rNIS-enhanced green fluorescent protein (eGFP) or hNIS-eGFP. The transfection efficiency of Ad/eGFP/rNIS and Ad/eGFP/hNIS to rBMSCs was measured by real-time polymerase chain reaction, flow cytometry, Western blot, and immunofluorescence staining. The transfected rBMSCs were transplanted into infarcted rat myocardium followed by a single-photon emission computed tomography (SPECT) study with 99m Tc-pertechnetate as the radiotracer and by autoradiography. The isolated rBMSCs were CD29, CD44, and CD90 positive and CD34, CD45, and CD11b negative. The expression of rNIS and hNIS in the transfected rBMSCs at both gene and protein levels was obviously higher than that without transfection. The myocardium of rats transplanted with transfected rBMSCs could be visualized by SPECT owing to the accumulation of 99m Tc-pertechnetate in rBMSCs mediated by exogenous NIS genes. The accumulation of 99m Tc-pertechnetate in myocardium mediated by rNIS was higher than that by hNIS , which was also confirmed by autoradiography. Both rNIS and hNIS are useful reporter genes to monitor BMSCs transplanted into infarcted myocardium in vivo with rNIS being superior to hNIS as the reporter gene.